Endobronchial Coil System versus Standard-of-Care Medical Management in the Treatment of Subjects with Severe Emphysema - Klooster, Karin; Valipour, Arschang; Marquette, Charles-Hugo; Boutros, Jacques; Mal, Hervé; Marceau, Armelle; Shah, Pallav L.; Conway, Francesca; Deslée, Gaëtan; Bourdin, Arnaud; Pison, Christophe; Grah, Christian; et al. (Respiration, 2021)
Abstract Background: Bronchoscopic lung volume reduction using endobronchial coils is a new treatment for patients with severe emphysema. To date, the benefits have been modest and have been suggested to be much larger in patients with severe hyperinflation and nonmulti-comorbidity. Objective: We aimed to evaluate the efficacy and safety of endobronchial coil treatment in a randomized multicenter clinical trial using optimized patient selection. Method: Patients with severe emphysema on HRCT scan with severe hyperinflation (residual volume [RV] ≥200% predicted and RV/total lung capacity [TLC] >55%) were randomized to coil treatment or control. Primary outcome measures were differences in the forced expiratory volume in 1 s (FEV1) and St George’s Respiratory Questionnaire (SGRQ) total score at 6 months. Results: Due to premature study termination, a total of 120 patients (age 63 ± 7 years, FEV1 29 ± 7% predicted, RV 251 ± 41% predicted, RV/TLC 67 ± 6%, and SGRQ 58 ± 13 points), instead of 210 patients, were randomized. At study termination, 91 patients (57 coil and 34 control) had 6-month results available. Analyses showed significantly greater improvements in favor of the coil group. The increase in FEV1 was greater in the coil group than that in the control group by + 10.3 [+4.7 to +16.0] % and in SGRQ by −10.6 [−15.9 to −5.4] points. At study termination, there were 5 (6.8%) deaths in the coil cohort reported. Conclusion: Despite early study termination, coil treatment compared to control results in a significant improvement in the lung function and quality of life benefits for up to 6 months in patients with emphysema and severe hyperinflation. These improvements were of clinical importance but were associated with a higher likelihood of serious adverse events.